(untitled) (Research, Society and Development, 2020)
The essay results from a qualitative study about “The National Humanization Policy/PNH” and its method of the triple inclusion and social participation of managers, health workers and users of / in SUS. It addresses conceptual aspects from the theoretical sociological, anthropological and historical assumptions of Simmel, Mauss and Foucault. Starting from the inclusion and social participation categories recommended by the PNH, a hermeneutic-dialectic analysis was carried out of the interviews of health professionals, managers and users, in humanization activities in two federal hospital units in Rio de Janeiro. The social construction of health care and management is analyzed, particularly the communication processes of different protagonists of the PNH/HumanizaSUS. As a result of the qualitative analysis of the interviews, anchored in the aforementioned theories, the essay postulates theoretical-practical correlation between the PNH method and the triadic circulation - giving-receiving-giving back - the word as a gift in humanization practices in / from SUS.